0620 A Long-Term Safety and Maintenance of Efficacy Study of Solriamfetol (JZP-110) in the Treatment of Excessive Sleepiness in Subjects with Narcolepsy or Obstructive Sleep Apnea. (27th April 2018) - Malhotra, A; Shapiro, C; Pepin, J; Hedner, J; Ahmed, M; Foldvary-Schaefer, N; Strollo, P; Mayer, G; Sarmiento, K; Baladi, M; Li, J; Chandler, P; et al.
Abstract: Introduction: Excessive sleepiness (ES) is a prominent symptom of narcolepsy and obstructive sleep apnea (OSA). Solriamfetol, a dopamine/norepinephrine reuptake inhibitor, was effective in the treatment of ES in narcolepsy and in OSA in 6-week and 12-week phase 3 studies. This study evaluated the long-term safety and maintenance of efficacy of solriamfetol. Methods: Subjects with narcolepsy or OSA who had completed prior studies with solriamfetol were eligible. Subjects began treatment with solriamfetol in the 2-week Titration phase followed by a Maintenance phase up to 50 weeks. A 2-week placebo-controlled Randomized Withdrawal (RW) was conducted after 6 months of treatment. Change from beginning to end of the RW in Epworth Sleepiness Scale (ESS) was the primary endpoint; Patient and Clinician Global Impression of Change (PGI-C and CGI-C, respectively) were secondary endpoints. Results: At the interim analysis, which included ongoing open-label and complete RW data, 638 subjects (226 narcolepsy; 412 OSA) had taken solriamfetol. Of these, 280 subjects (141 receiving placebo and 139 receiving solriamfetol) completed the RW (modified intent-to-treat population). At the end of the RW, ESS score increased by 1.6 (least squares [LS] mean) for the solriamfetol group compared with an increase of 5.3 (LS mean) for the placebo group ( P <0.0001). For both secondary endpoints, a greater percentage of subjects in the placebo group was reported as worse at the end of the RW compared with the solriamfetol group (both P <0.0001). Long-term maintenance of efficacy was also demonstrated during the open-label period up to 1 year by sustained reductions in mean ESS scores and improvements in PGI-C and CGI-C. The most frequent treatment-emergent adverse events (AEs; ≥5%) with solriamfetol were headache, nausea, insomnia, nasopharyngitis, dry mouth, and anxiety; 19 (2.9%) subjects experienced one or more serious AEs. Conclusion: These results demonstrate long-term maintenance of efficacy with solriamfetol in the treatment of ES in subjects with narcolepsy or OSA. The safety profile was consistent with prior placebo-controlled studies of solriamfetol. Support (If Any): Jazz Pharmaceuticals.